PERBASASI BASEBALL SPORTS BRANCH DEVELOPMENT MANAGEMENT (ALL INDONESIAN SOFTBALL BASEBALL UNION) PROVINCIAL MANAGEMENT OF DKI JAKARTA - Muhammad Fajar In’am Maulana; Teguh Santoso; Joko Sulistyono (Journal Of Indonesia Sport Education and Adapted Physical Education (JISEAPE), 2024)
The aim of this research is to find out (1) The organizational structure of the Perbasasi (All-Indonesian Baseball Softball Association) in the Perbasasi Management of DKI Jakarta Province. (2) What is the system for nurturing and developing young and senior athletes in the sport of Baseball in Perbasasi Pengprov DKI Jakarta. (3) What is the selection and coaching system for PON baseball athletes in Perbasasi Pengprov DKI Jakarta. (4) How are the coaches handling the DKI Jakarta Province Baseball Sport Branch for XX PAPUA PON 2022. (5) What are the facilities and infrastructure for the Baseball sport branch in the DKI Jakarta Provincial Pengbasasi. (6) What are the sources and management of funding in the DKI Jakarta Pengprov Perbasasi. The research method used is descriptive qualitative. Data collection techniques use 3 methods, namely (1) Observation (2) Interview (3) Documentation. Data source obtained from DKI Jakarta Perbasasi administrators, Head coach of the DKI Jakarta PON Baseball team and DKI Jakarta PON Baseball athletes. Technical Data Analysis uses Triangulation. Conclusions that the research illustrates. (1) Scope of Organization Perbasasi DKI Jakarta is a legal organization based on the laws of AD ART and the legality of SK which is still active, officially a member of KONI DKI Jakarta. (2) Early Childhood Nursery and Development is running well, with the collaboration of DKI Jakarta provincial administrators with associations in collaborating on early age nursery and coaching, by holding many tournament events and evenly providing guidance to early age athletes. (3) The DKI Jakarta PON Baseball athlete selection system is running well, the official team is serious in carrying out the selection, really paying attention to the aspects that are applied, through a 6 month journey the official team really carried out the selection carefully of 68 athletes to a quota of 20 athletes. (4) The range of coaches is very experienced, especially the head coach of the DKI Jakarta PON Baseball team. Gilberto Risanto Sajogo has had career experience as part of the official Indonesian National Baseball Team at the Asian Games and Sea Games as well as being an assistant coach from 2011 until he became head coach at PON Papua yesterday. and brought back the gold medal achievement. (5) Facilities and infrastructure to support the team undergoing a training program are very adequate, with the achievement sports category, baseball is fully supported by KONI DKI Jakarta in terms of equipment. With the large number of balls, legal bats, pitching machines, standard fields, this is a plus point for the DKI Jakarta baseball team in undergoing a training program. (6) Funding at Perbasasi DKI Jakarta, Perbasasi is a priority sports organization category at KONI DKI Jakarta, with a number of achievements in national events and many DKI Jakarta players being part of the Indonesian national baseball team making baseball a priority at KONI DKI Jakarta. All forms of funds received through good accountability reporting are carried out by the management to KONI DKI Jakarta.